Antifungal Activity of Citronella Grass (Cymbopogon nardus L. rendle) Extract Against Candida albicans in vitro - Utomo, Oki Saraswati; Handayani, Sutartinah Sri; Dharmawan, Ruben (Nexus Biomedika, 2016)
Introduction: Fungal infections caused by Candida sp. called by candidiasis or candidosis. Citronella Grass (Cymbopogon nardus L. rendle) is one of the plants that have a potential as an alternative antifungal treatment against Candida albicans because Citronella grass has saponin, flavonoids, tannins and essential oil which has a role as an antifungal. This study aims to determine the effect of Citronella Grass (Cymbopogon nardus L. rendle) extract as antifungal against the growth of Candida albicans in vitro. Methods: This research was a quasi experimental laboratory. The subjects in this study was subcultured of Candida albicans which was obtained from Laboratory of Parasitology and Mycology of the Faculty of Medicine, Sebelas Maret University, Surakarta. The research used 10 treatment groups, there was PEG 2% as negative control, Citronella Grass (Cymbopogon nardus L. rendle) extract which dissolved with PEG 400M so it was obtained 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100% for each concentration also ketoconazole 25 µg as positive control. The subjects were inoculated onto Saboraud Dextrose Agar which has 6 mm diameter well. The results was analyzed using One Way Anova and Post Hoc LSD. Results: All concentration levels of Citronella Grass extract showed activity against Candida albicans. The inhibition diameter increased with increasing concentrations. Extract with 100% concentration showed the highest antifungal activity even though the antfungal activity was lower than ketoconazole 25 µg. The average of inhibition diameter zone formed with concentration of 100% is 23.83 mm, meanwhile inhibition diameter zone of ketoconazole 25 µg is 27.50 mm. The results of statistical analysis using One Way Anova test showed that there are significant differences on ten treatment groups with the score p = 0.000 (p < 0.05). Negative control and positive control group also showed a significant difference in all groups. Conclusion: Citronella Grass (Cymbopogon nardus L. rendle) extract showed antifungal effect against the growth of Candida albicans in vitro start from concentration of 30% up to 100%, but that antifungal effect still less than ketoconazole 25 µg. Keywords: Antifungal, Citronella Extract, Candida albicans.